Neural Networks and Their Applications - Bishop, Christopher (Review of Scientific Instruments, 1994)
Neural networks provide a range of powerful new techniques for solving problems in pattern recognition, data analysis, and control. They have several notable features including high processing speeds and the ability to learn the solution to a problem from a set of examples. The majority of practical applications of neural networks currently make use of two basic network models. We describe these models in detail and explain the various techniques used to train them. Next we discuss a number of key issues which must be addressed when applying neural networks to practical problems, and highlight several potential pitfalls. Finally, we survey the various classes of problem which may be addressed using neural networks, and we illustrate them with a variety of successful applications drawn from a range of fields. It is intended that this review should be accessible to readers with no previous knowledge of neural networks, and yet also provide new insights for those already making practical use of these techniques.